Diminished hedonic capacity in social activities as a mediator of the link between dysfunctional behavioral activation system and depressive symptoms - Kuan, Chi-son; Liu, Qian-yu; Xu, Gang-min; Zhou, Han-yu; Nie, Jia-hui; Yan, Chao (Frontiers in Psychiatry, 2024)
Background Adolescence is a crucial period for the development of depression, and previous studies have suggested that the Behavioral Activation System (BAS) plays a significant role. However, little is known about the underlying mechanisms. This study aimed to explore the mediating role of anhedonia in the relationship between BAS and depressive symptoms among Chinese adolescents. Method A total of 1,023 high-school students aged 15–18 years participated in the study, with 916 continuing their participation three months later. All participants completed the Behavioral Inhibition System/Activation System (BIS/BAS) scale, Dimensional Anhedonia Rating Scale (DARS), Children’s Depression Inventory (CDI), and the State-Trait Anxiety Inventory (STAI-S/T). Pathway model analysis was performed to examine the concurrent and prospective mediating effects of anhedonia and the potential moderating effect of sex. Result Anhedonia in the domains of social activities, hobbies and sensory experiences significantly mediated the cross-sectional relationship between BAS and depressive level three months later. Furthermore, the beta-value of the mediating effect of social activities was significantly higher than that of the other domains of hedonic capacity cross-sectionally and longitudinally. However, sex showed no significant moderating effect. Conclusion Our findings underscore the importance of hedonic capacity, especially within the social domain, in the development of depressive symptoms. These findings contribute to the early diagnosis and prevention of depressive disorders.